Canadian travel survey, reallocated expenditures, by trip characteristics, 2000 - 2004 - Statistics Canada (Government of Canada, 2017)
This table contains 726 series, with data for years 1996 - 2004 (not all combinations necessarily have data for all years), and is no longer being released. This table contains data described by the following dimensions (Not all combinations are available): Geography, province of destination (11 items: Canada; Newfoundland and Labrador; Prince Edward Island; Nova Scotia; ...), Travel characteristics (35 items: Travel duration, total, same day and overnight travel; Travel duration, same day; Travel duration, overnight; Point of origin expenditures; ...), Type of travel duration (2 items: Total visits; Overnight visits).